Contribution of peptidyl prolyl isomerase (Pin1) to development of pulmonary hypertension via pulmonary vascular endothelial cell dysfunction. (25th November 2020) - Sakai, S; Maruyama, H; Ieda, M
Abstract: Background: Endothelial dysfunction is thought to be a major contributor to overall pathogenesis of vasculopathy seen in pulmonary hypertension (PH), which is manifested by the impaired release of nitric oxide (NO) generated through endothelial nitric oxide synthase (eNOS) in endothelial cells. Activation of human eNOS is regulated by phosphorylation at multiple sites including Thr33 and Ser114, which residues are followed by Pro. The peptidyl isomerase Pin1 specifically isomerizes the phospho-protein having Ser/Thr-Pro bond and regulates their activity. Pin1 is involved in proliferation, cell cycle, and apoptosis in cancer, by isomerizing some functional molecules such as JNK, JUN, cyclin D, BAX, etc. However, it is controversial whether direct interaction of Pin1 with eNOS and how eNOS activity is altered by Pin1, especially in PH. Purpose: We aimed to clarify whether Pin1 contributes to the PH development using Pin1 knockout mice and Pin1 affects the expression of phosphorylated eNOS (p-eNOS) molecule and pulmonary arterial endothelial cell (PAEC) apoptosis. Methods and results: Wild (WT) and Pin1-deficient mice (KO) were exposed to hypoxia (10% O2) or normoxia for 3 weeks to generate hypoxia-induced PH. Hypoxia-inducible factor (HIF1α) expression in lungs was significantly enhanced in WT-hypoxia (WH, n=6) and KO-hypoxia (KH, n=6), suggesting that hypoxic response was certainly occurred in these mice. Pulmonary arterial pressure did not elevate in KH compared with KO-normoxia (KN, n=6) and WT-normoxia (WN, n=6), it was significantly increased only in WH (P<0.01), indicating that KO did not develop PH by hypoxia. The gain of RV weight was parallel to the increase of pulmonary arterial pressure. Western blot showed that p-eNOS expression in lungs was significantly decreased in WH compared to WN, however, the expression was not different between KH and KN. It suggests that Pin1 plays a regulatory role in p-eNOS expression in hypoxic response. In cultured PAECs, the expression of p-eNOS and eNOS was markedly increased by siRNA-mediated Pin1 knockdown. Immunoprecipitation study showed the possibility of Pin1 binding to p-eNOS molecule. Apoptosis evaluated by caspase-3/7 activity by fluorescent assay and cleaved caspase-3 expression by Western blot was significantly increased by Pin1 overexpression in PAECs; however, it was significantly decreased by Pin1 knockdown. Moreover, the exaggeration of apoptosis induced by doxorubicin was markedly increased by Pin1 overexpression compared with control in PAECs; however, it was clearly suppressed by Pin1 knockdown. Conclusion: This study suggests that endogenous Pin1 contributes to the development of PH partly via the dysfunction of PAECs, that is, by the interference with p-eNOS expression and by the increase of apoptosis inducibility to external stimuli. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): JSPS KAKENHI